Metode Pembelajaran Matematika dengan Permainan di Kotamadya Pare-pare - Erawaty, Nur; Amir, Amir Kamal; Aris, Naimah; Kasbawati, Kasbawati; Sahriman, Sitti; Rangkuti, Aidawayati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The achievement of Mathematics contestants from the City of Pare-pare is very concerning. In February 2017elementary school mathematics competition was held. Of the 82 participants from Pare-pare, there were only 13 studentswho got scores above zero. Other students get zero or less than zero (negative). In March 2018, from 17 MathematicsEvent XVIII 2018 participants from Pare-pare, only 5 students had got positive scores. There was a decrease in interestand achievement in Mathematics in elementary school students in Pare-pare. The solution offered was training forMathematics Elementary School teachers by emphasizing learning method with playing. This is intended so that childrenhave enjoyed Mathematics from the beginning so that in the future the interest in learning Mathematics will be evengreater